1987
DOI: 10.1063/1.98139
|View full text |Cite
|
Sign up to set email alerts
|

Detection and measurement of local distortions in a semiconductor layered structure by convergent-beam electron diffraction

Abstract: It is shown that local tetragonal distortion in a Si Ge0.05Si0.95 strained-layered structure can be detected and quantified from analyses of the high-order Laue zone lines which are present in the bright-field disks of [001] convergent-beam electron diffraction patterns. The detection of a tetragonal distortion is based on symmetry arguments, whereas the quantification requires a detailed analysis which is based on computer simulated patterns, assuming a kinematical approximation of the scattering process and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

1989
1989
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 7 publications
1
10
0
Order By: Relevance
“…In general, there are tetragonal distortions in bulk strained-layer superlattices (SLSs) of cubic materials, such as Si/Ge. It has also been reported that the strain distributions in SLSs thinned in their cross-section for EM observation are slightly different from those in bulk SLSs (before thinning) due to strain relaxation in the thinned direction (Gibson and Treacy, 1984;Gibson et al, 1985;Maher et al, 1987). However, our multislice calculations indicate that these uniform distortions in Ge and Si layers have no significant effect on the results of the calculations; this agrees with a recent report (Stenkamp and Jä ger, 1993).…”
Section: Imaging Conditions For Si/gesupporting
confidence: 94%
“…In general, there are tetragonal distortions in bulk strained-layer superlattices (SLSs) of cubic materials, such as Si/Ge. It has also been reported that the strain distributions in SLSs thinned in their cross-section for EM observation are slightly different from those in bulk SLSs (before thinning) due to strain relaxation in the thinned direction (Gibson and Treacy, 1984;Gibson et al, 1985;Maher et al, 1987). However, our multislice calculations indicate that these uniform distortions in Ge and Si layers have no significant effect on the results of the calculations; this agrees with a recent report (Stenkamp and Jä ger, 1993).…”
Section: Imaging Conditions For Si/gesupporting
confidence: 94%
“…As already asserted, if there are no dislocations, there is no relaxation along the X2 direction in which the sample size can be considered as infinité ; hence a2x = a0 = 0.54288 nm. However, it may occur in practice that in the TEM sample the condition under which equation (16) has been derived is not realized, so that the cell of the SiGe alloy becomes slightly orthorhombic (ai, :5 a3x) [26]. Consequently the ratio R is slightly lesser than that reported in equation (18).…”
mentioning
confidence: 49%
“…Using the relation ͑6͒ the mismatch values reported in the fifth column are obtained; these are in good agreement with the DCD perpendicular mismatch value. Our method has been applied to the data obtained by Maher et al, 3 and the results are reported in the table as well ͑sample B͒.…”
Section: Sige/simentioning
confidence: 99%